Perkembangan Mu’jam al-‘Arabiyyah: Kajian Historis Tokoh dan Lembaga dalam Pengembangan Bahasa Arab - Saputra, Andre (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The mu’jam or dictionary represents a fundamental instrument in the preservation and development of the Arabic language, as well as a medium for learning among non-Arab speakers. This study aims to examine the historical development of mu’jam al-‘arabiyyah from the classical to the modern period, to trace the contributions of its major compilers, and to identify the institutions involved in the codification of Arabic both nationally and internationally. The research employs a library-based method by reviewing various sources, including books, articles, journals, and relevant online references. The findings reveal that the compilation of mu’jam began in the 2nd century H with al-Khalil ibn Ahmad al-Farahidi’s al-‘Ain, followed by classical figures such as Ibn Duraid, al-Azhari, Ibn Faris, Ibn Sidah, and Ibn Manzur. In the modern period, new works emerged, including al-Mu‘jam al-Wasīṭ, al-Mu‘jam al-Kabīr, and al-Mu‘jam al-‘Arabī al-Asāsī, along with digital and online dictionaries. In Indonesia, the development of mu’jam was marked by the publication of dictionaries authored by A.W. Munawwir and Mahmud Yunus, as well as official editions issued by the Ministry of Religious Affairs. Institutions that have contributed to the compilation of mu’jam include the National Language Development and Fostering Agency, the LPMQ of the Ministry of Religious Affairs, Islamic boarding schools (pesantren), private publishing houses, and international bodies such as Majma‘ al-Lughah al-‘Arabiyyah in Cairo and ALECSO. These findings affirm the vital role of mu’jam in ensuring the continuity of the Arabic language and supporting its teaching and learning in diverse contexts.